Recent progress of bioinspired interfacial materials towards efficient and sustainable scale resistance. (August 2022) - Wang, Yixuan; Wang, Shutao; Meng, Jingxin
Abstract: Inspired by nature, anti-fouling materials have attracted great attention for reducing the deposition of undesirable objects (e.g., ice, wax and scale), displaying promising applications in daily life and industrial production. Due to annoying hazards of scale deposition such as energy wasting and pipeline clogging, increased interest has paid on the theme of bioinspired interfacial materials with efficient and sustainable scale resistance. In this review, we first summarized the recent progress of bioinspired anti-scaling interfacial materials by utilizing proper mediums (i.e., air, oil and water) as barrier layers. Then, the related theory of barrier-mediated scale resistance was proposed from inhibiting interfacial nucleation and adhesion of mineral crystals. Later, some promising strategies were provided for improving the durability and sustainability of barrier layers such as structure-mimic strategy for air barrier, internal releasing and external supplying strategy for oil barrier, and enhanced hydration for water barrier. Finally, some challenges and perspectives were raised for developing advanced anti-scaling interfacial materials. Therefore, this review may afford great inspirations to develop advanced materials and technologies with unparalleled anti-scaling for conquering scaling problems, alleviating energy shortage and assisting double carbon goals. Graphica abstract: Image, graphical abstract